Pengembangan modul perawatan balita dan deteksi dini stunting secara mandiri - Vivianti Dewi; Gusti Lestari Handayani; Abbasiah Abbasiah; Ermiati Ermiati; Triyana Harlia Putri (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: The World Bank in 2006 also stated that stunting, which is chronic malnutrition that occurs in the womb and during the first two years of a child's life, can result in low intelligence and reduced physical capacity, which ultimately leads to reduced productivity, slowed economic growth and prolongation of poverty. The problem is that not all mothers have sufficient knowledge to be able to detect health problems experienced by their family members, especially mothers who have children. For this reason, guidelines are needed that can help mothers detect stunting early in the form of a module.Purpose: To produce educational media products in the form of modules for early detection of stunting which is intended for mothers with children under five.Method: The research was carried out by distributing pre-test and post-test questionnaires and providing a module on early detection of stunting. This research uses Quasi Experiment (Pre-test post-test design). 94 mothers who have children under five who live in the Jambi Province, namely Muaro Jambi, Kerinci and East Tanjung Jabung were sampled using a purposive sampling technique. Analysis used are univariate and bivariate. The statistical test used is the T-Dependent test.Results: The results of the analysis of the average knowledge of respondents before being given the early detection and treatment module for stunting toddlers was 16.26 on early detection of stunting and 17.54 on how to care for stunting toddlers. Meanwhile, the average knowledge of respondents after being given health education was 21.22 on early detection of stunted toddlers and 22.49 on how to care for stunted toddlers. The results of statistical tests obtained a p-value of 0.000, there was a difference in knowledge between before and after being given the module.Conclusion: There is a difference in respondents knowledge before and after being given the early detection and treatment module for stunting toddlers.Keywords: Early Detection; Independent; Module Development; Stunting Incidents.Pendahuluan: World Bank pada tahun 2006 juga menyatakan bahwa stunting yang merupakan malnutrisi kronis yang terjadi didalam rahim dan selama dua tahun pertama kehidupan anak dapat mengakibatkan rendahnya intelegensi dan turunnya kapasitas fisik yang pada akhirnya menyebabkan penurunan produktivitas, perlambatan pertumbuhan ekonomi, dan perpanjangan kemiskinan. Permasalahannya tidak semua ibu mempunyai pengetahuan yang cukup untuk dapat mendeteksi masalah-masalah kesehatan yang dialami anggota keluarganya, terutama sekali bagi ibu yang memiliki anak. Untuk itu diperlukan pedoman yang dapat membantu ibu dalam mendeteksi dini kejadian stunting berupa sebuah modul.Tujuan: Menghasilkan produk media edukasi berbentuk modul untuk mendeteksi dini kejadian stunting yang diperuntukkan bagi ibu dengan anak balita.Metode: Penelitian dilakukan dengan cara menyebarkan kuesioner pre-test dan post-test diberikannya modul tentang deteksi dini stunting. Penelitian ini menggunakan Quasi Eksperimen (Pre-test post-test design). 94 orang ibu yang mempunyai anak balita yang berdomisili diwilayah Provinsi Jambi yaitu Muarojambi, Kerinci dan Tanjung Jabung Timur dijadikan sampel dengan teknik purposive sampling. Analisis yang digunakan adalah univariat dan bivariat. Uji statistic yang digunakan yakni uji T-Dependent.Hasil: Hasil analisis rata-rata pengetahuan responden sebelum diberikan modul deteksi dini dan perawatan pada balita stunting adalah 16,26 pada deteksi dini stunting dan 17,54 pada cara perawatan balita stunting. Sedangkan rata-rata pengetahuan responden setelah diberikan pendidikan kesehatan adalah 21,22 pada deteksi dini balita stunting dan 22,49 pada cara perawatan pada balita stunting. Hasil uji statistic didapatkan p-value 0,000 terdapat perbedaan pengetahuan antara sebelum dan sesudah diberikan modul.Simpulan: Ada perbedaan pengetahuan responden sebelum dan sesudah diberikan modul deteksi dini dan perawatan pada balita stunting.